2021
DOI: 10.1016/j.sjbs.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged humoral and cellular immunity in COVID-19-recovered patients

Abstract: By the beginning of 2021, the battle against coronavirus disease 2019 (COVID-19) remains ongoing. Investigating the adaptive immune response against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19, in patients who have recovered from this disease could contribute to our understanding of the natural host immune response. We enrolled 38 participants in this study. 7 healthy participants and 31 COVID-19 patients who had recovered from COVID-19 and categorized them into 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…It remained high 90 days after the infection in some individuals indicating long-term and steady antibody levels. Intriguingly, the male participants had notably higher anti-S IgG levels after recovery than females, as seen in other works reflecting sex-dependent humoral immune response against SARS CoV-2 ( 36 , 37 ). There was also a significant positive correlation between the patients’ age and their anti-S IgG antibody levels, showing a greater concentration in older adults compared to younger adults.…”
Section: Humoral Immunity During Covid-19 Infection and Recovery Stagesupporting
confidence: 77%
See 2 more Smart Citations
“…It remained high 90 days after the infection in some individuals indicating long-term and steady antibody levels. Intriguingly, the male participants had notably higher anti-S IgG levels after recovery than females, as seen in other works reflecting sex-dependent humoral immune response against SARS CoV-2 ( 36 , 37 ). There was also a significant positive correlation between the patients’ age and their anti-S IgG antibody levels, showing a greater concentration in older adults compared to younger adults.…”
Section: Humoral Immunity During Covid-19 Infection and Recovery Stagesupporting
confidence: 77%
“…Recovered patients who presented with mild symptoms showed a noticeable rise in the percentage of B cells compared to healthy individuals. Despite specific anti-S IgG in all COVID-19 patients, regardless of how severe the symptoms are, a rise was seen in this antibody level as well ( 36 ). It remained high 90 days after the infection in some individuals indicating long-term and steady antibody levels.…”
Section: Humoral Immunity During Covid-19 Infection and Recovery Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Studies that compare data between men and women are also necessary to investigate potential sex differences among adults. Furthermore, investigations exploring the level of cellular immunity in asymptomatic individuals are necessary, as a recent study showed that patients with asymptomatic SARS-CoV-2 infection had a significantly increased natural killer (NK) cells fraction compared with the healthy, non-infected group, suggesting that NK cells may serve as an indicator of asymptomatic infections [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a memory immune response could provide protection against reinfection [ 28 ], and the persistence of the IgG antibody has been identified over the long-term in COVID-19-recovered patients with different disease presentations [ 29 ]. Moreover, a recent study showed prolonged humoral as well as cellular immunity in recovered COVID-19 patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%